A Novel Technique Identifies Valve-Like Pathways Entering and Exiting Schlemm’s Canal in Macaca nemestrina Primates With Similarities to Human Pathways - Martin, Elizabeth A.; Johnstone, Murray A. (Frontiers in Cell and Developmental Biology, 2022)
Purpose: 1) To describe a novel combination of techniques that permit immunohistochemistry imaging of Schlemm’s canal inlet (SIV) and outlet (SOV) valve-like structures. 2) To identify tissue-level SIV adhesive relationships linking the trabecular meshwork (TM) to hinged collagen leaflets at Schlemm’s canal (SC) external wall. 3) To determine whether the SIV lumen wall’s adhesive vascular markers are like those of SC inner wall endothelium. Materials and Methods: Anterior segments of 15 Macaca nemestrina primates underwent IHC labeling. We perfused fluorescent microspheres into 12 of the eyes. Limbal tissues were divided into quadrants, viscoelastic introduced into SC, tissues fixed, immunohistochemistry done, radial segments cut, tissues clarified, and confocal microscopy performed. Finally, we generated ImageJ 3D projections encompassing the TM, SC, and distal pathways. Results: IHC imaging identified 3D relationships between SIV, collector channel ostia, collector channels (CC), SOV, and intrascleral channels. Imaging depth increased 179% following clarification (p<0.0001). Imaging demonstrated CD31, Collagen Type 1, and 4 in the walls of the SIV lumen and more distal pathways. In eight eyes, 384 segments were examined, 447 SIV identified, and 15.4% contained microspheres. Conclusions: Our technique’s imaging depth permitted the identification of SIV linkage between the TM and SOV. We found comparable cell-cell adhesion molecules (CD31) and basement membrane components in SC inner wall and the SIV lumen walls. Recent OCT studies suggest that SIV tensional relationships may control CC entrance dimensions that regulate distal resistance. Cellular adhesive properties sustain SIV tensional relationships. These SIV cell-cell, cell-basement membrane properties warrant further study because abnormalities could be a factor in the IOP elevation of glaucoma.